Pemanfaatan Artifical Intellegence Dalam Pembelajaran Bahasa Arab Di Madrasah Aliyah Negeri 2 Kulon Progo - Setiawan Setiawan; Maslamah Maslamah (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This research aims to describe the concept of Artificial Intelligence and analyze the use of Artificial Intelligence in learning Arabic at MAN 2 Kulon Progo. This type of research is qualitative research with description and explanation methods. Data collection techniques in this research are through observation and documentation. The data analysis technique is carried out in three stages, namely: data collection, data reduction and drawing conclusions. Meanwhile, the technique for validating the research data is through data triangulation, including source, technique and time. The results of this research show that; 1 Artificial Intelligence (AI) has the characteristics of Acting Humanly, Thinking Humanly, Think Rationally, Act Rationally. The way AI works in learning is as follows: Personalization, Flexible, Adaptive, Collaboration, Innovation. This AI has advantages and disadvantages when used in learning Arabic. 2. The use of AI in learning Arabic at MAN 2 Kulon Progo has been implemented in the four Arabic language skills, with the following details: 1) Listening Skills (al-Maharah al- Istima') with the veed.io website, 2) Speaking Skills (al-Maharah al-Kalam) with the Instagram and TikTok applications, 3) Reading Skills (al-Maharah al-Qira'ah) with Google Lens and the almaany.com website, 4) Writing Skills (al-Maharah al-Kitabah) with the Bing translator and Canva websites.